Do we Need New Methodology in Macroeconomics? - Pacho, Wojciech (Warsaw Forum of Economic Sociology, 2010)
The questions whether methodology employed by mainstream macroeconomics is sufficient and whether and in what extent innovative propositions in that field are in demand appears to of growing importance. In this article the concept of the role of representative agent for developments in economic science is thoroughly discussed. The strengths and deficiencies of the Representative Agent Model are examined.